عصر حاضر میں معاشی استحکام کی حکمت عملی:حالات ِپاکستان کے تناظر میں سیرت النبیﷺ کا انطباقی مطالعہ: Strategies for economic stability in contemporary times:An Adapted Study of the Seerah in pakistani circumstances - komal shehzadi,; Dr Hafiz Muhammad Hassan, (Seerat Studies, 2023)
Abstract Islam is a complete code of life & Life style of Prophet (Uswah Rasool) covers all aspects of life from civilization and culture to economy and society. Undoubtedly, the guiding principles of every aspect of human affairs can be derived from the life of the Messenger of Allah. The significance of Sirat-ul-Nabi as a guide for economic stability and the role of religion in economic development are both examined in the study. A literature review, data collection, and analysis of primary and secondary sources are all included in the research design. According to the research, Sirat-ul-Nabi may be able to offer direction for Pakistan's economy. Based on Sirat-ul-Nabi, the study identifies key economic stability strategies, such as fostering social justice, supporting entrepreneurship, and emphasizing the value of ethical behavior in business. Discussions about the findings' implications for stakeholders and policymakers are included, along with ideas for further study. Overall, this study adds to the body of knowledge on the subject and sheds light on Sirat-ul-Nabi's potential as a manual for Pakistan's economic stability. Keywords: Pakistan, Economic Stability, Strategy, Religion, Business Ethics.